2017
DOI: 10.1002/adom.201601103
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Resonator‐Based Metasurface: An Ultrabroadband and Near‐Unity Absorption

Abstract: Water-resonator-based metasurface : an ultrabroadband and near-unity absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(54 citation statements)
references
References 43 publications
0
52
0
Order By: Relevance
“…Although water enjoys the advantage of high real part of permittivity in microwave regime, its imaginary part is also high, which indicates a large absorption to the microwave. Hence, water-cell metamaterials are proposed as perfect absorbers for microwave [122][123][124]. The water can be patterned as droplet array with a metallic reflector at the backside which blocks the transmission of the microwave.…”
Section: Water-cell Metamaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although water enjoys the advantage of high real part of permittivity in microwave regime, its imaginary part is also high, which indicates a large absorption to the microwave. Hence, water-cell metamaterials are proposed as perfect absorbers for microwave [122][123][124]. The water can be patterned as droplet array with a metallic reflector at the backside which blocks the transmission of the microwave.…”
Section: Water-cell Metamaterialsmentioning
confidence: 99%
“…The liquid background metamaterial consists metamaterial in water solvent [56], metamaterial in Lc [88] and nanoparticles in liquid [98]. The liquid-cell metamaterial consists of water-cell metamaterial [124] and liquid-metal-cell metamaterial [140].…”
Section: Introductionmentioning
confidence: 99%
“…Liquid dielectric antennas have drawn a significant amount of attention for a number of reasons, (1) conformability: any antenna shape can be achieved due to the nature of liquid; (2) reconfigurability (both physical and chemical): it is easy to change the resonance frequency and bandwidth by changing the height/width of the liquid stream and the chemical composition; (3) low cost: liquid dielectrics are cheap and easily available compared to more costly liquid metals (e.g., mercury (Hg) or eutectic gallium indium allow (EGaIn)), (4) transparent and biocompatible, (5) high permittivity which helps to miniaturize antennas. Besides antennas, liquid dielectric materials have been applied in the field of metamaterials and metasurfaces [14][15][16][17], for the design of reconfigurable frequency selective surfaces (FSS) [18], absorbers [19][20][21][22][23], sensors [24], reflect-arrays and array lenses [25], and polarization converters [18]. However, these topics fall beyond the scope of the present review and the details can be found in the review papers [15,26].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, innovative results have been achieved in the field of metamaterials, namely, artificial structures that exhibit electromagnetic, acoustical, and optical properties that are generally not found in nature. From the moment of the first experimental verification of the single negative metamaterials [1,2], the unique properties based on negative permittivity, permeability or index of refraction have found a place in a number of novel devices and applications [3][4][5][6][7][8]. Special attention has been given to double-negative or left-handed (LH) media, which at the same time show negative values of permittivity and permeability in a certain frequency range.…”
Section: Introductionmentioning
confidence: 99%